Green-field Architecture for Sustainable Supply Chain Strategy Formulation - Petar Radanliev (International Journal of Supply Chain Management, 2015)
The focus of this paper is on supply chain strate- gy formulation. A conceptual theory approach is used for investigating and identifying the relationship between multi- ple elements, dimensions, forces and factors that influence and affect the supply chain strategy formulation in Green- field context, specific to the slate mining industry. The re- search study involved secondary data review and series of 20 qualitative interviews, followed by 2 group discussions, one with mining and transportation experts external to the sup- ply chain and one group discussion with supply chain inter- nal experts. Through critical analysis, a number of problems emerge and the process of addressing these problems, results in a new framework for evaluating the relationship between business and supply chain strategy, specific to Greenfield project and integration design context.
Keywords: L23; L72; L60; L50; 330; Supply chain strategy; supply chain formulation; supply chain architecture; supply chain design